Synthesis and Bioactivities of Novel 1,3,4-Thiadiazole Derivatives of Glucosides - Chen, Meihang; Zhang, Xun; Lu, Daowang; Luo, Hairong; Zhou, Zengyan; Qin, Xufeng; Wu, Wenneng; Zhang, Guoping (Frontiers in Chemistry, 2021)
A series of novel 1,3,4-thiadiazole amide derivatives containing glucoside moiety were synthesized and characterized by 1H NMR, 13C NMR, and HRMS. Then, their antifungal activities against Gibberella zeae (G. zeae), Botryosphaeria dothidea (B. dothidea), Phompsis sp, Phytophthora infestans (P. infestans), and Thanatephorus cucumeris (T. cucumeris) and antibacterial activities against Xanthomonas oryzae pv. oryzae (Xoo) and Xanthomonas citri subsp. citri (Xcc) were investigated in vitro. Biological activity test showed that some of the target compounds exhibited good activities. Especially, the compounds 4i and 4q showed higher bioactivities against P. infestans, with the EC50 values of 3.43 and 5.02 μg/mL, respectively, than that of Dimethomorph (5.52 μg/mL). While, the target compounds showed lower antibacterial activities against Xoo and Xcc at 200 and 100 μg/mL than those of Thiodiazole-copper.